First record of Pseudaeginella arraialensis (Amphipoda: Caprellidea) from the Gulf of Mexico - Ignacio Winfield; José M. Guerra-García (Revista Mexicana de Biodiversidad)
During a sampling campaign in Puerto Progreso, Yucatán, Mexico, several specimens of the caprellid Pseudaeginella arraialensis were collected. They were attached to buoys as part of fouling communities between 0.5-12 m depth. The present study represents the first record of P. arraialensis for the Gulf of Mexico, increasing its geographical distribution range 7,500 km northwards, from Arraial do Cabo, Brazil to Puerto Progreso, Mexico, SW Gulf of Mexico.